Computing Level of Privacy in a Virtual Environment. (March 2013) - Indraprastha, Aswin; Shinozaki, Michihiko
This paper presents a computational model designed to analyze architectural space and to a develop privacy level using two methods: visual distance method and viewing angle method as those are primary cognitive mechanism to experience architectural space. We suggest that the result will offer possibilities for quantitative design analysis of privacy that influenced by architectural elements. The proposed method consists of two stages: determination of subdivided enclosed spaces and measuring privacy level on each subdivided enclosed space. Previous models showed that spatial quality is related to the visual distance to the architectural elements. In addition to distance variables, our model includes viewing angle variables to determine area and the direction angle from any observation point to the architectural elements on the boundary of an interior space. The case study evaluation is able to rank the quality of design of interior spaces with respect to their privacy level.